Evaluating Prognostic Factors for Liver Transplantation Among United States Patients With Hereditary Transthyretin-Mediated (hATTR) Amyloidosis Using National Registry Data. (September 2019) - Brandman, Danielle; Lin, Hollis; McManus, Anastasia; Agarwal, Sonalee; Gache, Larry M.; Irish, William; Gollob, Jared; Živković, Saša A
Introduction: Orthotopic liver transplantation has been used as a treatment for hereditary transthyretin-mediated (hATTR) amyloidosis, a rare, progressive, and multisystem disease. Research Question: The objective is to evaluate survival outcomes post-liver transplantation in patients with hATTR amyloidosis in the United States and assess whether previously published prognostic factors of patient survival in hATTR amyloidosis are generalizable to the US population. Design: This cohort study examined patients with hATTR amyloidosis undergoing liver transplant in the United States (N = 168) between March 2002 and March 2016 using data reported to the Organ Procurement and Transplantation Network (UNOS)/United Network for Organ Sharing (OPTN). Results: A multivariable Cox hazards regression model showed among all factors tested, only modified body mass index (kg/m 2 × g/L) at the time of transplant was significantly associated with survival. Higher modified BMI was associated with lower risk of death relative to a reference population (<600) with historically poor post-transplant outcomes. Patients with modified BMI 1000 to <1200 (hazard ratio [HR] = 0.27; 95% confidence interval [CI] = 0.10-0.73), 1200 to <1400 (HR = 0.20; 95% CI = 0.06-0.75), and ≥1400 (HR = 0.15; 95% CI = 0.04-0.61) exhibited improved adjusted 5-year post-transplant survival of 74%, 80%, and 85%, respectively, versus 33% in the reference population. Discussion: The association between a higher modified BMI threshold at the time of transplant and improved post-transplant survival suggests that the previously published patient selection criterion for modified BMI may not be applicable to the US population.